Strategies for improving the competitiveness of business in developing countries through the use of information systems. - ELLIOT, Stephen R. (1995)
Examines the strategic information systems/technology (IS/T) decision-making practices of indigenous firms in a developing country. Develops a framework of good practice to assist such enterprises in their strategic use of IS/T for improved competitiveness.